Hubungan Pengetahuan dan Dukungan Keluarga terhadap Status Depresi pada pasien Kanker Serviks di RSUD DR. H. Abdul Moelok Bandar Lampung Tahun 2016 - Ratna Dewi PS; Anggraeni Janar Wulan; Shesy sya’haya (Medula, 2020)
Cervical cancer is the second most types of cancer experienced by women around the world and are most numerous in Latin America and developing countries such as Indonesia. The impact that occurs in patients with cervical cancer one of which can cause problems in people with depression. Depression will be overcome by their patients use coping mechanisms based on the resources around. Source coping is important for the patient is the knowledge and family support. The study was to determine the related knowledge and family support for the level of depression in patients with cervical cancer at the Dr. H. Abdul Moeloek Bandar Lampung Hospital in 2016. The study is analytic survey with cross sectional approach. The sampling method using purposive sampling and obtained a sample of 24 respondents. The study uses chi square test with an alpha of 0.05. Results research showed a significant relationship between knowledge with the depressed levels of cervical cancer patients were obtained by value p = 0.014 and there was a significant relationship between family support with the depressed levels of cervical cancer patients were obtained value of p = 0.023. Theres a significant relationship knowledge and family support for the level of depression in patients with cervical cancer at the Dr. H. Abdul Moeloek Bandar Lampung Hospital in 2016